Gazdasági változások Széchenyi István gróf Zala vármegyei birtokain (1814-1860) = Economic changes on the estates of count István Széchenyi in Zala County (1814-1860) - Kaposi, Zoltán (Közép-Európai Közlemények, 2018)
István Széchenyi is a well-known public figure of the national Economic History. His economic activity is mostly remembered by his foundations and innovations in the secondary and the tertiary sector. We have less information though how the once great landowner (possessing 95,000 acres) managed his demesnes inherited from his father and what results his management had. Count Széchenyi sold his Demesne of Csokonya (located in Somogy County) to his brothers, which accounted for 60% of his lands. After it he was left with only three smaller demesnes and two of them (Demesne of Szentgyörgyvár and Demesne of Pölöske) were in Zala County. In this study, we examine what purpose these demesnes in Zala County fulfilled beside the manor of Nagycenk (next to the City of Sopron) which was developed into a model farm. Were there efforts to modernise those two demesnes? What was the operating system of those two demesnes in Zala County like? How did they try to benefit from the agricultural boom of the 1830-40s? The primary conclusion of our examination is that there were some initiative steps to restructure and improve the demesnes in Zala County (sheep husbandry, vinery and winery, transforming moorland to meadows by draining them) but the owner was most concerned with the sure profit he gained.